Robust Admissibility and H? Performance of Time-Varying Descriptor Systems - Acosta-Barbosa, K (2013)
This paper addresses the problems of admissibility and H? performance analysis for continuous-time linear time-varying (LTV) descriptor systems. Firstly, necessary and sufficient conditions are proposed to ascertain the admissibility of LTV descriptor systems based on the Lyapunov theory. Secondly, admissibility and H? performance analysis results are derived to deal with linear parameter-varying descriptor systems, where the parameters and their time-derivatives are supposed to be bounded with known limits. These results are then cast in terms of parameter-dependent strict linear matrix inequalities (LMIs) considering affine and polynomial parameter-dependent Lyapunov functions. A numerical example illustrates the proposed approach. © 2013 IEEE.